2016
DOI: 10.1097/mjt.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Intravenous Lidocaine for the Treatment of Complex Regional Pain Syndrome: A Case Report and Literature Review

Abstract: Complex regional pain syndrome (CRPS) was described in 1864 by Mitchell et al as a condition characterized by many unique symptoms. Although symptoms may differ from patient to patient, the most common complaints are painful swelling in upper or lower extremities or changes in the skin. CRPS has been given many different names since it was first mentioned in the literature in 1851. The most common alternative names include causalgia, aglodystrophy, and sympathetic dystrophy syndrome. This condition is generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Of the two children, one received a 5% lidocaine local patch ( 10 ) and the other received a local block of 0.5% lidocaine 15 mL and 0.25% bupivacaine 20 mL, followed by an intravenous infusion of 250 mg lidocaine ( 11 ). Among the six adult patients, a 26-year-old patient was given intravenous medication at 1–2mg/kg/h for 4 h ( 12 ), one patient was given 5% lidocaine ointment three times a day ( 13 ), and four patients were given a local block therapy with combination medication ( 11 , 14 16 ). Except for one patient who received a systemic infusion of lidocaine and ketamine without any pain relief ( 17 ), all the other patients achieved varying degrees of pain relief, of which two patients did not achieve sustained pain relief ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two children, one received a 5% lidocaine local patch ( 10 ) and the other received a local block of 0.5% lidocaine 15 mL and 0.25% bupivacaine 20 mL, followed by an intravenous infusion of 250 mg lidocaine ( 11 ). Among the six adult patients, a 26-year-old patient was given intravenous medication at 1–2mg/kg/h for 4 h ( 12 ), one patient was given 5% lidocaine ointment three times a day ( 13 ), and four patients were given a local block therapy with combination medication ( 11 , 14 16 ). Except for one patient who received a systemic infusion of lidocaine and ketamine without any pain relief ( 17 ), all the other patients achieved varying degrees of pain relief, of which two patients did not achieve sustained pain relief ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of safety, we found that high concentrations of systemic lidocaine were more likely to cause adverse effects, including nausea, dizziness, fatigue, bradycardia, tachycardia, and atrial arrhythmias ( Table 3 ) ( 12 , 19 ). The adverse reactions in patients using lidocaine patches were mild, mainly skin reactions, which could be recovered after drug withdrawal ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beside other recommended or possible treatments ( 56 , 57 ), intravenous regional anesthesia (Bier block) is the most used modality of lidocaine administration for the treatment of CRPS. Whether lidocaine is used alone ( 58 - 60 ) or in combination with guanetidine ( 61 ), after the Bier block, the patients successfully improved their motor function.…”
Section: Evidence Acquisitionmentioning
confidence: 99%